2003
DOI: 10.1038/sj.eye.6700496
|View full text |Cite
|
Sign up to set email alerts
|

Improving on ETDRS acuities: design and results for a computerised thresholding device

Abstract: Aims All visual acuity data are subject to test-retest variability (TRV). This measurement error obscures true clinical change and reduces the statistical power of clinical trials using acuity as a primary outcome measure. This study was designed to assess whether a computerised system can reduce TRV by taking repeated acuity measurements and averaging them. A computerised system (PC-test) was developed for this purpose and compared in terms of TRV with the current Gold Standard ETDRS logMAR chart. Methods A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 13 publications
(15 reference statements)
1
30
0
Order By: Relevance
“…Although the system allows the versatility to test discrimination under other levels of contrast, illumination, and hue, in this study, normal values are reported only for high-contrast white targets presented against a black screen in a darkened room (99% Michelson contrast, background 1.0 Cd/M 2 ). Visual acuity, as determined with the ETDRS chart, averaged 1.15 ± 0.37 arc min MAR (20/23), which compares with prior studies using the same chart, 32 whereas the acuity thresholded at fixation by the perimetry system averaged 1.75±0.85 arc min MAR (20/35) representing 0.6 arc min MAR poorer than the ETDRS acuity. This difference may have been due to the short presentation time of the Landolt Cs (250 ms) compared with the average duration of fixation that is usually taken to read each letter of the acuity chart (usually to 0.5-1 s or more).…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Although the system allows the versatility to test discrimination under other levels of contrast, illumination, and hue, in this study, normal values are reported only for high-contrast white targets presented against a black screen in a darkened room (99% Michelson contrast, background 1.0 Cd/M 2 ). Visual acuity, as determined with the ETDRS chart, averaged 1.15 ± 0.37 arc min MAR (20/23), which compares with prior studies using the same chart, 32 whereas the acuity thresholded at fixation by the perimetry system averaged 1.75±0.85 arc min MAR (20/35) representing 0.6 arc min MAR poorer than the ETDRS acuity. This difference may have been due to the short presentation time of the Landolt Cs (250 ms) compared with the average duration of fixation that is usually taken to read each letter of the acuity chart (usually to 0.5-1 s or more).…”
Section: Discussionsupporting
confidence: 41%
“…Comparing nasal vs temporal presentations, or superior vs inferior, we observed no significant differences at any eccentricity with a two-tailed, paired t-test at Po0.05, results similar to that of prior studies. 32,39,[44][45][46] Refixations may potentially produce artifacts in the measurement of the acuities at the locations close to fixation. However, for an eccentric stimulus to initiate a saccade in the appropriate direction, it must persist for at least a minimum time of 100-120 ms for detection, 47 after which the saccade would require B20-35 ms to complete the refixation over the angular distance, and thereafter, the target must remain for at least 150-180 m for discriminatory function to ascertain the correct C orientation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the accurate acuity test, a test-retest strategy designed to enhance the sensitivity of logMAR acuity testing. 24 Despite using this exhaustive strategy, we were unable to show an improvement (or a decrement) in binocular photopic UCVA, photopic BCVA, or mesopic BCVA in patients with the Z9000 IOL. Although small increments in visual acuity performance have been detected in some studies, 8,11,15 most found no significant gains with the Z9000 IOL.…”
Section: Discussionmentioning
confidence: 74%
“…Visual acuities were recorded using the Accurate Acuity Test, a test-retest protocol designed to increase the accuracy and repeatability of logMAR acuity testing. 24 Scotopic and low and high mesopic pupil diameters were recorded in both eyes using a P2000 infrared pupillometer (Procyon Instruments Ltd.). 25 Patients were then examined briefly at the slitlamp with an undilated pupil to exclude gross IOL decentration.…”
Section: Methodsmentioning
confidence: 99%